Assessing genetic diversity of tomato (Solanum lycopersicum) genotypes cultivated under protected condition - GAUTAM, RAVI; SINGH, PRAVEEN K; HUSSIAN, ZAKIR; TOMER, B S; SINGH, A K; RUDRA, SHALINI GAUR; LAL, SANDEEP KUMAR; KUMAR, JUGENDRA (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during 2018–19 and 2019–20 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate 16 quantitative and qualitative traits of 36 genotypes of Tomato (Solanum lycopersicum L.) and to examine the genetic variability and character association between yield and its component traits. This investigation involved correlation and genetic divergence analyses to gain insights into the relationships among the various traits. The variance analysis revealed notable variations among genotypes, indicating a substantial level of genetic diversity among them. Among the genotypes, 178 and 115 were found promising for both yield and quality traits. Genotype no. 178 was found superior for fruit weight and yield. The principal component analysis indicated that the first 3 components i.e. component 1 (equatorial diameter, average fruit weight and fruit weight uniformity); component 2 (number of locule and equatorial/polar index); and component 3 (number of fruit and number of fruit/cluster) collectively accounted for 81.48% of the variability. The yield exhibited significant positive correlation with average fruit weight (g), pericarp thickness (cm), polar diameter of fruit (cm), equatorial diameter of fruits (cm) and average fruit weight after each harvest (kg).